THE FUNCTION AND SIGNIFICANCE OF HUMAN RESOURCE INFORMATION SYSTEMS (HRIS) FOR BUSINESS COMPETITIVENESS (International Journal of Food and Nutritional Sciences, 2023)
The functionality of human resource (HR) functions in today's organisations has been revolutionised by human resource information systems (HRIS). HR professionals can now carry out HR tasks and provide prompt, pertinent HR services easily and effectively thanks to HRIS, which was not possible with manual information processing and sharing. HRIS is becoming increasingly important, useful, and necessary, but not all organisations have been able to exploit it to its full potential. The purpose of this paper is to shed light on this situation from three different angles: first, how HRIS has evolved over time at various organisations for managing HR; second, the HR functions that are used through HRIS; third, the enabling and impeding factors for the best use of HRIS; and finally, the challenges that are currently facing HRIS from the users' and management's perspectives.